Patients' attitudes to the summary care record and HealthSpace: qualitative study. Issue 7656 (29th May 2008) - Greenhalgh, Trisha; Wood, Gary W; Bratan, Tanja; Stramer, Katja; Hinder, Susan
Abstract : Objective To document the views of patients and the public towards the summary care record (SCR, a centrally stored medical record drawn from the general practice record) and HealthSpace (a personal health organiser accessible through the internet from which people can view their SCR), with a particular focus on those with low health literacy, potentially stigmatising conditions, or difficulties accessing health care. Design 103 semistructured individual interviews and seven focus groups. Setting Three early adopter primary care trusts in England where the SCR and HealthSpace are being piloted. All were in areas of relative socioeconomic deprivation. Participants Individual participants were recruited from general practice surgeries, walk-in centres, out of hours centres, and accident and emergency departments. Participants in focus groups were recruited through voluntary sector organisations; they comprised advocates of vulnerable groups and advocates of people who speak limited English; people with HIV; users of mental health services; young adults; elderly people; and participants of a drug rehabilitation programme. Methods Participants were asked if they had received information about the SCR and HealthSpace and about their views on shared electronic records in different circumstances. Results Most people were not aware of the SCR or HealthSpace and did not recall receiving information about it. They saw both benefits and drawbacks to having an SCR and described a process of weighing the former against the latter when making their personal choice. Key factors influencing this choice included the nature of any illness (especially whether it was likely to lead to emergency care needs); past and present experience of healthcare and government surveillance; the person's level of engagement and health literacy; and their trust and confidence in the primary healthcare team and the wider NHS. Overall, people with stigmatising illness were more positive about the SCR than people who claimed to speak for "vulnerable groups." Misconceptions about the SCR were common, especially confusion about what data it contained and who would have access to it. Most people were not interested in recording their medical data or accessing their SCR via HealthSpace, but some saw the potential for this new technology to support self management and lay care for those with chronic illness. Conclusion Despite an extensive information programme in early adopter sites, the public remains unclear about current policy on shared electronic records, though most people view these as a positive development. The "implied consent" model for creating and accessing a person's SCR should be revisited, perhaps in favour of "consent to view" at the point of access.